THE ROLE OF PHILOSOPHY IN THE SYSTEM OF SOCIAL SCIENCES AND HUMANITIES (Scientific journal of the Fergana State University, 2024)
This article examines the classification of sciences in the modern era, social sciences, the history of their origin, the attitude to social sciences today, the role of philosophy in the system of social sciences and its impact on the upbringing of harmoniously developed youth.